Effects of Intrauterine Inflammation on Cortical Gray Matter of Near-Term Lambs - Stojanovska, Vanesa; Atik, Anzari; Nitsos, Ilias; Skiöld, Béatrice; Barton, Samantha K.; Zahra, Valerie A.; Rodgers, Karyn; Hooper, Stuart B.; Polglase, Graeme R.; Galinsky, Robert (Frontiers in Pediatrics, 2018)
Introduction: Ventilation causes cerebral white matter inflammation and injury, which is exacerbated by intrauterine inflammation. However, the effects on cortical gray matter are not well-known. Our aim was to examine the effect of ventilation on the cerebral cortex of near-term lambs exposed to intrauterine inflammation. Method:Pregnant ewes at 119 ± 1 days gestation received an intra-amniotic injection of saline or lipopolysaccharide (LPS; 10 mg). Seven days later, lambs were randomized to either a high tidal volume injurious ventilation strategy (INJSALN = 6, INJLPSN = 5) or a protective ventilation strategy (PROTSALN = 5, PROTLPSN = 6). Respiratory parameters, heart rate and blood gases were monitored during the neonatal period. At post-mortem, the brain was collected and processed for immunohistochemical assessment. Neuronal density (NeuN), apoptotic cell death (caspase 8 and TUNEL), microglial density (Iba-1), astrocytic density (GFAP), and vascular protein extravasation (sheep serum) were assessed within the frontal, parietal, temporal and occipital lobes of the cerebral cortex. Results:A significant reduction in the number of neurons in all cortical layers except 4 was observed in LPS-exposed lambs compared to controls (layer #1: p = 0.041; layers #2 + 3: p = 0.023; layers #5 + 6: p = 0.016). LPS treatment caused a significant increase in gray matter area, indicative of edema. LPS+ventilation did not cause apoptotic cell death in the gray matter. Astrogliosis was not observed following PROT or INJ ventilation, with or without LPS exposure. LPS exposure was associated with vascular protein extravasation. Conclusion:Ventilation had little effect on gray matter inflammation and injury. Intrauterine inflammation reduced neuronal cell density, caused edema of the cortical gray matter, and blood vessel extravasation in the brain of near-term lambs.